Biological control against locusts expands - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Negotiations with three companies have begun for the commercial production and sale of Green Muscle®, the biological insecticide for use against locusts and grasshoppers. Mass commercialisation will make it widely available to farmers who face...